Prevalencia de parásitos intestinales con riesgo zoonótico en Canis lupus familiaris de la localidad de Retes, Lima, Perú - Naupay I., Asucena (2019)
The aim of this study was to determine the prevalence of intestinal parasites and the risk factors associated with zoonotic transmission in dogs with owner in the rural town of Retes, Huaral district (Lima, Peru). A descriptive cross-sectional study was carried out, where fecal samples of 47 dogs were collected and processed by simple direct methods, Willis-Molloy flotation technique and the rapid sedimentation technique modified by Lumbreras. The morphometric identification of the parasitic species was also done. The statistical analysis was performed by bivariate analysis with Chi square distribution. The prevalence of enteroparasitosis was 31.9%. Dipylidium caninum (12.8%), Toxocara canis (10.6%), Ancylostoma spp (4.3%), Cystoisospora canis (4.3%), Taenia spp (2.1%) were found. Monoparasitism was 76.7%, followed by biparasitism (13.4%) between helminths and protozoa. The feeding site was the only risk factor associated with intestinal parasitism (OR=7.11, X2=5.23, p=0.03). Dog’s zoonotic helminths D. caninum, T. canis and Ancylostoma spp, given the prevalence found, could easily be transmitted to humans because they are occupying the same habitat in the rural area of Huaral.